Visual Orbits of Spectroscopic Binaries with the CHARA Array. IV. HD 61859, HD 89822, HD 109510, and HD 191692 - Lester, Kathryn V.; Schaefer, Gail H.; Fekel, Francis C.; Gies, Douglas R.; Henry, Todd J.; Jao, Wei-Chun; Paredes, Leonardo A.; Hubbard-James, Hodari-Sadiki; Farrington, Christopher D.; Gordon, Kathryn D.; Chojnowski, S. Drew; Monnier, John D.; et al. (The Astronomical journal, 2022)
We present the visual orbits of four spectroscopic binary stars, HD 61859, HD 89822, HD 109510, and HD 191692, using long baseline interferometry with the CHARA Array. We also obtained new radial velocities from echelle spectra using the APO 3.5 m, CTIO 1.5 m, and Fairborn Observatory 2.0 m telescopes. By combining the astrometric and spectroscopic observations, we solve for the full, three-dimensional orbits and determine the stellar masses to 1%–12% uncertainty and distances to 0.4%–6% uncertainty. We then estimate the effective temperature and radius of each component star through Doppler tomography and spectral energy distribution analyses. We found masses of 1.4–3.5 M ⊙ , radii of 1.5–4.7 R ⊙ , and temperatures of 6400–10,300 K. We then compare the observed stellar parameters to the predictions of the stellar evolution models, but found that only one of our systems fits well with the evolutionary models.